Filozofija jezika in Rajhmanova filozofska misel - Juhant, Janez (Edinost in dialog, 2025)
Jože Rajhman largely developed his philosophical language and his philosophical-theological perspective in spiritual dialogue with God and in dialogue with the social and ecclesiastical currents of the time. An influential pastoral-theological paradigm for him was the work of (Slovenian) Protestants in the demanding and changing conditions of their proclamation of God's message to Slovenians. The development of the Slovenian and theological language and the theological speech of other nations was significantly influenced by the Second Vatican Council with its liturgy in the native language and pastoral approaches, the »modernization« (»aggiornamento«) of the Church's work, which required a language appropriate to the feelings of modern man. Speech is for him an essential tool of preaching. Rajhman's understanding of language and philosophy thus served the best possible understanding of the word of God and its theological elaboration, which would reach modern man, especially Christians. Trubar and the Protestants were his examples for this. Following their example, his goal was the best possible pastoral mobility of the Church. His study of Trubar and the Protestants also inspired the formation of guidelines for the pastoral work of the Church in modern times. He approached the demanding Slovenian conditions of the Church under communism with special interest and the position of liberation theology. Together with Grmič, they searched for the elements of the so-called socialist theology. The article attempts to evaluate Rajhman's pastoral-theological project, with an appropriate time distance and critical approach and linguistic analytical attention, and to place it in the context of the development of theological discourse, especially the Second Vatican Council and the pastoral conditions of the Church in the Slovenian socialist reality, and in general in the demanding conditions of the »modern« world and humanity.
Keywords: "posodabljanje"; "socialist theology"; "socialistična teologija"; "updating"; discourse; drugi vatikanski cerkveni zbor; filozofija; govorica; Holy Scripture; philosophy; Protestantism in Slovenia; protestantizem na Slovenskem; Rajhman, Jože; Second Vatican Council; Sveto pismo; teologija; theology